2007
DOI: 10.1039/b615335f
|View full text |Cite
|
Sign up to set email alerts
|

Gold(i)-catalysed arylation of 1,6-enynes: different site reactivity of cyclopropyl gold carbenes

Abstract: Gold(I)-catalysed addition of electron-rich arenes and heteroarenes to 1,6-enynes gives two different types of products by reaction of the intermediate cyclopropyl gold carbenes at the cyclopropane or at the carbene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
73
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 154 publications
(79 citation statements)
references
References 36 publications
4
73
0
2
Order By: Relevance
“…The research group of Echavarren observed independently a similar reactivity of 1,6-enynes. [180] It is interesting to note that the reactivity of the presumed gold carbene intermediate 457 [see Scheme 36 and Eqs. (149) and (150) Polycyclic heterocycles bearing an oxygen bridge were obtained by a tandem cyclization/Prins reaction.…”
Section: Methodsmentioning
confidence: 99%
“…The research group of Echavarren observed independently a similar reactivity of 1,6-enynes. [180] It is interesting to note that the reactivity of the presumed gold carbene intermediate 457 [see Scheme 36 and Eqs. (149) and (150) Polycyclic heterocycles bearing an oxygen bridge were obtained by a tandem cyclization/Prins reaction.…”
Section: Methodsmentioning
confidence: 99%
“…(180)]. [203] Der Mechanismus dieser Tandemreaktion wurde bisher noch nicht untersucht; sie verläuft vermutlich aber über ein Metallacyclopenten (ähnlich zu 530, Schema 41 [205] Die Cycloaddition von 544 beispielsweise verlief glatt und führte zum funktionalisierten Siebenringderivat 545 [Gl.…”
Section: Enin-tandemreaktionenunclassified
“…[11][12][13] Recently, the Au I -catalyzed additions of carbon nucleophiles to 1,6-enynes via intermediates 3 have been described. [14,15] A few unsubstituted 1,6-enynes (1, RЈ = H), as well as those bearing alkyl or aryl substituents at the alkyne, can cyclize by endo pathways via intermediates 6 (Scheme 1) to give bicyclic compounds 7. [11,16,17,18] We have found recently that opening of gold(I) intermediates 6 to form seven-membered ring products is also possible.…”
Section: Introductionmentioning
confidence: 99%